2014 8th. Malaysian Software Engineering Conference (MySEC) 2014
DOI: 10.1109/mysec.2014.6985996
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid architecture for one-stop e-government portal integration and interoperability

Abstract: An effective one-stop e-government portal needs egovernment system with good integration and interoperability. However, most e-government portals lack in integration and interoperability. This problem causes each government agency tend to have its own portal. Hence, it prevents the government to provide services in a single access point. Therefore, e-government system needs a better architecture for integration and interoperability among e-government system components, applications, and services. The architect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…At the higher stage of Digital Government evolution, the problem of interoperability arises and becomes one of the main obstacles of further Digital Government development Cellary and Strykowski (2009). Therefore, the study of interoperability in Digital Government has increased in recent years, and researchers are developing interoperable architectures for Digital Government (see for example (Marques et al 2011;Sedek et al 2014;Luna-Reyes et al 2012;Paul and Paul 2012;Guijarro 2007)).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…At the higher stage of Digital Government evolution, the problem of interoperability arises and becomes one of the main obstacles of further Digital Government development Cellary and Strykowski (2009). Therefore, the study of interoperability in Digital Government has increased in recent years, and researchers are developing interoperable architectures for Digital Government (see for example (Marques et al 2011;Sedek et al 2014;Luna-Reyes et al 2012;Paul and Paul 2012;Guijarro 2007)).…”
Section: Related Workmentioning
confidence: 99%
“…Data Exchange or Government Enterprise Bus (Agarwal et al 2017;Zhang et al 2008;Sedek et al 2014;González et al 2012;Sedek et al 2012;Wei and Yan 2010;AlAbdali et al 2019) We found various names for this component such as Middle Layer, Middleware, Digital Government Service Bus, Interoperability Framework, Content Bus, or Enterprise Service Bus, in the literature, but same meaning.…”
Section: Security and Interoperabilitymentioning
confidence: 99%
“…Effective integration and interoperability e-government architecture involves integration of components and interoperability of applications and services. However, it is difficult because the huge number of agencies and services [19]. Integration approach for onboarding was proven success in Bristol-Myers Squibb which increase 92% their employees beliefs on productivity after one month on the job [20].…”
Section: Mapping Of Integrated Process Against Onboarding Goalsmentioning
confidence: 99%